El Intertestamento. La Biblia entre el Antiguo y el Nuevo Testamento. - Coria, Marcela (Scripta Mediaevalia, 2025)
The article focuses on the work *The Intertestament. The Bible between the Old and New Testament* by Jaime Vázquez Allegue, which offers a comprehensive overview of the biblical literature produced between approximately 150 B.C. and 150 A.D., a key period for understanding the historical and religious context surrounding the life of Jesus. The book addresses Hellenistic and Roman Judaism, Jewish groups, and intertestamental literary genres such as apocalyptic literature, apocrypha, the Dead Sea Scrolls, and rabbinic literature. It highlights the importance of these texts for biblical exegesis and presents the content in an accessible way for a broad audience, with a didactic approach that invites deeper exploration of this crucial moment in religious and cultural history.